KAJIAN SUKSES IMPLEMENTASI E-GOVERNMENT STUDI KASUS: PEMERINTAH KOTA BOGOR - Idrus, Iqbal Aidar; Zakiyah, Ummi; Hodiyah, Lisa (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2017)
Good governance is a conception of a clean, democratic, and effectivegovernment administration, and in it governs a synergistic and constructiverelationship between government, private business and the public. The use ofinformation technology that can improve the relationship between government andother parties. E-Government is an effort to develop electronic (electronic)governance in order to improve the quality of public services effectively and efficiently, new services, increased citizen participation and an enhancement to the global information infrastructure. Local Government is a forum for implementing EGovernment. Bogor City Government is one area that is considered successful implement e- government. Bogor City has initiated eGovernment initiatives since 2008-2009 long before the Inpres was issued and has successfully won numerous awards for its success in egovernment implementation. The results show that the overall implementation of E-Government has run well but has not been optimally accessing public involvement. Ease of e-government is only enjoyed by a small number of people who are familiar with information technology. The main challenge of e-government development is the ability and readiness of management and the culprits so it is not a mere technological sophistication. Key Word: E-Government, Local Government, Good Goverment